Aktiviti pemulihan bacaan di sebuah sekolah rendah: Satu kajian kes / Nor laila Bt Kuslan - Kuslan, Nor laila (2014)

(untitled)
The purpose of this study is to examine the operational activities of the remedial reading in a selected national primary school in Shah Alam, Selangor. Specifically, its main purpose is to explore how the teaching and learning process of the remedial reading is conducted and what are the factors that support or hinder the success of the activities. The respondents of the study consisted of 27 Year 1 remedial pupils, school administrators (Head Mistress and Academic Senior Assistant), the Remedial Teacher, Bahasa Melayu subject teachers of those remedial pupils, School Counsellors, Media Teacher, remedial pupils’ parents and Ministry Officials who are responsible for the Remedial Programme in the Ministry of Education Malaysia (MOE) and the State Education Department of Selangor. This study was conducted as a case study. The study focussed on the following aspects: how the remedial reading activities were implemented, and what are the factors that support or hinder the success of the implementation of the activities. The data collection is conducted through observation, semi-structured interviews, and document analysis in relation with remedial reading activities in the sample school. Three types of instruments were prepared to provide guidelines for the data collection namely, Interview Schedule, Anecdotal Observation Guidelines, and Document Analysis Guidelines. The documentation and data analysis was carried out simultaneously to maintain the validity of the data. In order to produce a holistic thick-description of the research, the data analysis was obtained in two phases, i.e., during and after the data collection. The impact of the research was observed through the sharing of ideas in the focus group in order to triangulate and maintain validity of the data. The researcher employed a narrative approach to report the findings vi in accordance with the respective groupings and sub-groupings which is based on the objectives and the research questions of the study. The result of the overall remedial reading activities in the school sample has shown that the activities, which were carried out at the operational/implemenatiton level, have been carried out in tandem with the Remedial Programme Guidelines of the MOE with some adjusted elements from the Remedial Teacher’s experieces and creativity to fulfill the requirements and the needs of the remedial pupils.The findings of the research concurred that Remedial Teacher, remedial programme facilities (infrastucture), the related teaching and learning remedial reading materials and support system at all levels formed the four critical success factors of the remedial reading activities implementation. On the contray, failure to pay attention to these same four factors could also contribute to the hinderence of a successful implementation of the remedial reading activities, besides the quality of the pupils and parental factors, ability of the pupils to understand the phonemic and semantic system of the learned language, in this case, Bahasa Melayu, and the interference of the pupils’ native language. Accordingly, all the factors that help in the success of the remedial reading activities should be strengthened whereas those factors that hinder its success should be remedied in order to reduce and to completely abolished the illiteracy rate among the primary school children.